'Trinity Professors versus Men of Letters: Ferguson, Dowden and De Vere' - Patten, Eve (My University, 2022)
This essay considers the relationships between Samuel Ferguson, Edward Dowden, and Aubrey de Vere in the late nineteenth century. In evaluating Ferguson’s career shortly after the poet’s death in 1886, W. B. Yeats considered him as being ill-served by the ‘English notions’ of Irish criticism, a slight which was particularly directed at Edward Dowden, then Professor of English at Trinity College Dublin. Rather than viewing this schism solely as a difference of opinion on Gaelic antiquarianism and Celtic Revivalism, this essay considers the divergence between these men as an effect of their respective positioning inside and outside the institutions of academia. It also interprets their relationship against the backdrop of public debates in the period about the nature of literary criticism as well as the role and function of the critic. Drawing on the correspondence between Ferguson, Dowden, and their mutual friend and frequent intermediary Aubrey de Vere, this essay examines how their friendship was affected by a growing distinction between the ‘man of letters’ and the professional academic in the later Victorian period. In particular, it offers an alternative view of Dowden, whose public commitment to the development of English Literature as an academic subject was sometimes belied by his private warmth towards Ferguson and his project of Celtic Revivalism.
PUBLISHED
Keywords: Creative Arts Practice; Identities in Transformation; Making Ireland; Manuscript, Book and Print Cultures; Language and/or Literature, Victorian; Culture; History; Literature